2009
DOI: 10.1001/archpediatrics.2009.63
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Strategies for Children With Asthma

Abstract: To evaluate the evidence that quality improvement (QI) strategies can improve the processes and outcomes of outpatient pediatric asthma care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 90 publications
1
56
0
1
Order By: Relevance
“…30 Bratava and colleagues showed in a meta-analysis that self management programs favour quality improvement in general -but there were multiple strategies used in the different studies. 31 Our findings -that asthma management provided by a hospital-based specialised asthma nurse is not inferior to management provided by a GP or a paediatrician -agrees with the earlier findings of Kamps et al 16 This may have important implications for the organisation of paediatric outpatient care. First, nurse-led outpatient management can be provided at a lower cost than medical care by a paediatrician.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…30 Bratava and colleagues showed in a meta-analysis that self management programs favour quality improvement in general -but there were multiple strategies used in the different studies. 31 Our findings -that asthma management provided by a hospital-based specialised asthma nurse is not inferior to management provided by a GP or a paediatrician -agrees with the earlier findings of Kamps et al 16 This may have important implications for the organisation of paediatric outpatient care. First, nurse-led outpatient management can be provided at a lower cost than medical care by a paediatrician.…”
Section: Discussionsupporting
confidence: 90%
“…We showed in an earlier paper 29 a small but statistically significant difference in ACQ between children treated in primary care and in hospital care, whereas all the other measured parameters showed no statistically significant difference. Publications by Kelly et al 30 and Bratava et al 31 slightly favour specialist care over primary care. However, the populations and health care settings in these studies differ considerably from the Dutch situation.…”
Section: Discussionmentioning
confidence: 97%
“…Practices should consider using allied health professionals to demonstrate or assess device technique with children with asthma when their providers do not have time to do so. [20][21][22][23][24] In addition to providers showing patients how to correctly use asthma devices, patients and their families could be encouraged to ask their community pharmacists about proper use of these devices. 8 Pharmacists can be a valuable resource for patients in providing counseling and education regarding inhaler use.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of 79 quality improvement interventions for children with asthma found that several types of interventions improved process and outcomes of care, although the magnitude of improvement was often modest. 41 Of the 6 studies that exclusively enrolled adolescent patients, none showed significant improvement in key asthma outcomes, such as medication use, asthma symptom control, or use of health services. In addition, these studies often did not quantitate the process improvements that were associated with improvement in outcomes.…”
mentioning
confidence: 99%